2019
DOI: 10.3847/1538-4357/ab053e
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Compact Groups of Galaxies through Cosmic Time

Abstract: We use the outputs of a semianalytical model of galaxy formation run on the Millennium Simulation to investigate the prevalence of 3D compact groups (CGs) of galaxies from z = 11 to 0. Our publicly available code identifies CGs using the 3D galaxy number density, the mass ratio of secondary+tertiary to the primary member, mass density in a surrounding shell, the relative velocities of candidate CG members, and a minimum CG membership of three. We adopt "default" values for the first three criteria, representin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…In fact, simulations suggest that 96 percent of compact groups at 𝑧 = 2 are fully merged into a single massive galaxy by 𝑧 = 0 (e.g. Wiens et al 2019), so we may be observing the IGrM in the early stages of that merger process. At low redshift, Chen et al (2019) used VLT/MUSE to observe the CGM in emission for a group of 14 galaxies associated with a known DLA in a background quasar spectrum.…”
Section: Tidal Streams From Galaxy Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, simulations suggest that 96 percent of compact groups at 𝑧 = 2 are fully merged into a single massive galaxy by 𝑧 = 0 (e.g. Wiens et al 2019), so we may be observing the IGrM in the early stages of that merger process. At low redshift, Chen et al (2019) used VLT/MUSE to observe the CGM in emission for a group of 14 galaxies associated with a known DLA in a background quasar spectrum.…”
Section: Tidal Streams From Galaxy Interactionsmentioning
confidence: 99%
“…Simulations have suggested that 95 percent of compact groups at 𝑧 = 2 will fully merge into a single galaxy by 𝑧 = 0 and up to ∼ 15 percent of galaxies were located in these environments in the past (e.g. Wiens et al 2019). Studying compact groups at earlier epochs can test these predictions.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that most of the criteria used in the literature are applied on flux limited samples in redshiftspace, with a few exceptions (see for instance, Wiens et al 2019).…”
Section: Ideal Compact Groups In 3d Real and Redshift Spacementioning
confidence: 99%
“…These works studied the 3D nature starting from observational CGs. From another point of view, Wiens et al (2019), using a particular set of semi-analytical galaxies, started from groups identified in 3D real space, and developed a criterion in 3D based on Hickson criteria. Their study focus in the evolution of the population of galaxies in CGs over cosmological time.…”
Section: Introductionmentioning
confidence: 99%
“…A suitable tool for such a study are the mock galaxy catalogues constructed using a semi-analytical model of galaxy formation (SAM) on top of a 𝑁-body cosmological simulation. During the last decade, such mock catalogues built from SAMs have been widely used to understand the frequency, nature and identification of CGs (McConnachie, Ellison & Patton 2008;Díaz-Giménez & Mamon 2010;Zandivarez et al 2014b;Díaz-Giménez & Zandivarez 2015;Taverna et al 2016;Díaz-Giménez, Zandivarez & Taverna 2018), as well as their mass assembly (Farhang et al 2017) and their frequency versus time (Wiens et al 2019). The nature of CGs has also been analysed from mock CGs extracted from hydrodynamical simulations (Hartsuiker & Ploeckinger 2020).…”
Section: Introductionmentioning
confidence: 99%